Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan PT. BPR Parasari - Krisna, I Made Agus Gita Wijaya; Satrya, I Gusti Bagus Honor (Jurnal Ilmiah Wahana Pendidikan, 2023)
Organizational success can be measured by the effectiveness of its employees. The research location is PT. BPR Parasari was chosen because it found employee performance problems caused by less harmonious relations between employees and employee mismatch in a field of work. This study aims to determine the effect of the work environment and work discipline on employee performance. Attribution theory is used as a theoretical basis. The population in this study were all employees of PT. BPR Parasari. The method of determining the sample using nonprobability sampling with saturated sampling technique so that the number of research respondents as many as 58 people. The data analysis technique used is multiple linear regression analysis, classical assumption test, model feasibility test, and T test. This study found that the work environment and work discipline have a positive and significant effect on employee performance; work environment has a positive and significant effect on employee performance; work discipline has a positive and significant effect on employee performance; work discipline has a more dominant influence on employee performance. The implications of this study explain that PT. BPR Parasari needs to improve the work environment and work discipline so that later it will improve employee performance.